A REVIEW OF THE BASIC ELEMENTS, ORGANIZATIONAL AND THEORETICAL FOUNDATIONS OF WORK-BASED LEARNING (WBL) IN THE HIGHER EDUCATION - J. Talbot; C. Costley; M. A. Dremina; V. A. Kopnov (Russian State Vocational Pedagogical University, 2017)
The aim of the study is to review basic elements, organizational and theoretical foundations of work-based learning (WBL) in the higher education, based mostly on the experience of higher education institutions in the United Kingdom.Methodology and research methods. The methods of system and comparative analysis, synthesis and generalization are used.Results. This review article summarizes briefly: the social attributes of students who prefer to complete WBL programs; relevant requirements of employers to the quality of training; a new university policy on the management of training, and its contribution to the creation of innovative educational environment at workplaces; overcoming challenges when establishing long-term partnerships between universities and enterprises; organizational and theoretical foundations of the WBL study programs. A number of critical remarks on WBL study programs are being analyzed. Authors make a point about the importance of a transdisciplinary shell framework to facilitate learning driven by the interests of the learner(s). When carrying out the review, authors refer also to the experience of other English-speaking countries (Australia and the USA), which also successfully develop the concept under consideration.Scientific novelty. For the first time an analytical review of basic elements, organizational and theoretical foundations of work-based learning (WBL) in the higher education, which is widespread in English-speaking countries over the last 25 years, is presented in the Russian scientific literature in education.Practical significance. The materials provided in the article can be useful to managers and teachers of higher education institutions, methodologists of higher and vocational education providers and departments of professional development of High-Tech enterprises.